2008
DOI: 10.1001/archotol.134.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Quality of Life After Nasal Surgery Alone for Patients With Obstructive Sleep Apnea and Nasal Obstruction

Abstract: To evaluate the impact of nasal surgery alone on quality of life (QOL) in patients with obstructive sleep apnea and nasal obstruction using generic and diseasespecific QOL questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 22 publications
5
102
2
3
Order By: Relevance
“…In most of these trials, no significant improvement was observed in the objective measures of PSG. Discrepant results in AHI and oxygen saturation level were revealed in previous studies (Table 4) [9,[17][18][19][20][21][22]. Our study showed no significant [16,17,23].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In most of these trials, no significant improvement was observed in the objective measures of PSG. Discrepant results in AHI and oxygen saturation level were revealed in previous studies (Table 4) [9,[17][18][19][20][21][22]. Our study showed no significant [16,17,23].…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, Nakata et al [18] reported a significant decrease in the ESS score after surgery. In the study of Li et al [22] which assessed the improvement in the quality of life of OSAS patients after nasal surgery, a significant improvement in the snoring outcome survey, bed partner survey, and ESS were found. The analysis of our subjective findings correlated with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…5 The authors undertook a prospective study of 51 patients with OSA and nasal obstruction due to nasal septal deviation. Patients completed the Snore Outcomes Survey (SOS), the Spouse/Bed Partners Survey (SBPS), the ESS, and Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) before and after septoplasty with partial inferior turbinate resection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The exact role of nasal obstruction in obstructive sleep apnea is unclear. One explanation can be represented by the reduced nasal cross sectional area which causes an increased nasal resistance and favours the inspiratory collapse of the oropharynx, hypopharynx, or both 19,20 .…”
Section: Upper Airway Permeabilization Surgery -Brief Literature Reviewmentioning
confidence: 99%